The Importance of Employment Contract for Umsida Quality Employees Improvement - Noor Fatimah Mediawati; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2015)
The absence of employment contracts in UMSIDA recognized cause some problems. Especially in improving the performance of employees. Issues a little more disturbing harmonious labor relations between employees and UMSIDA. In the terminology of the Labour Act, employment contract terms it is known as the Employment Agreement. Where the existence of labor agreement / contract employment is expected to harmonize the working relationship with the employer in accordance with the applicable rules. The existence of employment contracts is also a legal instrument which according to researchers ought to be put forward in efforts to increase the qualifications and competence of employees. By contract it will also avoid things that are not desirable in an employment relationship, because each party will always carry out their rights and responsibilities are aligned and balanced. Tranquility in the work and the guarantee of legal protection are expected to improve employee performance especially towards quality UMSIDA 2020. So this study explored further the urgency employment contract once its design. How To Cite: Mediawati, N., & Phahlevy, R. (2015). The Importance of Employment Contract for Umsida Quality Employees Improvement. Rechtsidee, 2(2), 141-156. doi:http://dx.doi.org/10.21070/jihr.v2i2.106